The effect of nutrition-related patterns on primary infertility among couples in Gaza Strip: A case-control study - Amal DHAIR; Maha NUBANI HUSSEINI; Yehia ABED (Journal of Health and Social Sciences)
Introduction: Nutritional health is one of the most controversial themes that had long been investigated against reproductive health. This study aimed to explore the relationship between different diet components and behaviour among infertile and fertile couples. Methods: A case-control study was conducted in Gaza Strip with the participation of 160 infertile couples matched residentially with 160 fertile ones. Infertile couples were chosen from patients who were registered in five fertility centers from 2016 to 2018. Data were collected through a self-administered questionnaire extended by the WHO STEP wise diet questionnaire and analyzed through SPSS program version 22 by using descriptive analysis, independent T-test, cross-tabulation, and logistic regression. Results: Our findings revealed that more infertile couples than fertile ones consume vegetables for less than 4 days/week (P = 0.001, females and males), less than 3 servings in each of these days (P < 0.001, females and males), less than 5 total servings of fruits and vegetables (P = 0.004 females, P = 0.010 males) and more red meat in main meals (P = 0.010 females, P = 0.042 males). Regular consumption of sweets and/or chips, soda and/or canned juice and using vegetable oil rather than olive oil also provided significant positive association (P = 0.031, P = 0.022, P = 0.020 respectively). Adjusting covariates showed that 65% of the risk is reduced by consumption of vegetables for more than 3 days/week (P = 0.007) and 54% reduction is achieved with every additional serving of vegetables consumed per day (P = 0.029). Conclusion: The study provides credible evidence for the importance of following healthy nutritional patterns that seems to offer remarkable protection against primary infertility.